Morphometrical Observations on the Thyroid Gland of Prenatal Goat (Capra hircus) - Sharma, Anamika (Indian Journal of Veterinary Anatomy, 2019)
Gross morphological studies were conducted on thyroid gland of goat foetii ranging from 51 to 134 daysÂ of gestation. The thyroid gland consisted of oval shaped left and right lobes connected by a narrow flattenedÂ band called isthmus. Both lobes were present on the ventro-lateral aspect of caudal part of larynx and initial part of trachea and extended upto 5th or 6th tracheal rings. The average length of the left lobe was more than right lobeÂ but average width and thickness of the right lobe were more than the left lobe.